1995
DOI: 10.1111/j.1399-0039.1995.tb02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HLA class II alleles by genotyping in a Manchu population in the northern part of China and its relationship with Han and Japanese populations

Abstract: The genetic polymorphism of the HLA class II loci was investigated in a Manchu population resident in the northern part of China and compared with those of other Asian populations including Japanese and Han. In 8 DQA1 alleles, the most frequent allele was DQA1*03 with the gene frequency of 25.5%. Of 15 DQB1 alleles tested, 11 were observed and the most common allele was DQB1*0301 with the gene frequency of 24.5%. Among 19 DPB1 alleles, 11 were detected and DPB1*0501 (43.8%) was the most frequent allele as obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 26 publications
5
39
0
Order By: Relevance
“…Sixty-seven other populations were included in the analyses for genetic comparisons and are detailed in the footnote of Figure 2; they come from different worldwide geographical locations (South, Central and North America, Mediterranean, East Asia, Australia and Pacific Islands) and belong to different ethnic groups (Amerindians, Siberian, Na-Dene, Eskimos, Caucasoids, Orientals, Australian aborigins, Polynesians, Melanesians and Micronesians). Populations used for study are: Mazatecos (Arnaiz-Villena, 2000); Seri (Petzl-Erler, 1997); Mixe (Petzl-Erler, 1997); Mixteco (Petzl-Erler, 1997); Zapoteco (Petzl-Erler, 1997); Mexican Mestizo (Unpublished); Arhuaco (Yunis, 1994); Kogi (Yunis, 1994); Arsario (Yunis, 1994); Cayapa (Titus- Trachtenberg, 1994); Xavante (Cerna, 1993); Guarani (Petzl-Erler, 1997); Toba-Pilaga (Cema, 1993) ; Mataco-Wichi (Cerna, 1993); Eastern-Toba ( Cerna, 1993); Jaidukama (Unpublished); Eskimos (Grahovac, 1998); Athabascans (Monsalve, 1998); Tlingit (Imanishi, 1992); Nivkhs (Grahovac, 1998); Udegeys (Grahovac, 1998); Koryaks (Grahovac, 1998); Chukchi ( Grahovac, 1998); Kets (Grahovac, 1998); Evenks (Imanishi, 1992); Singapure-Chinese (Imanishi, 1992); Buyi ( Imanishi, 1992); Manchu (Geng, 1995); Coreans (Imanishi, 1992); Japonese (Imanishi, 1992a,b); Khalk-Mongolians (Munkhbat, 1997); Tuvins (Martinez-Laso, 2001); Khoton-Mongolians (Munkhbat, 1997); Germans (Imanishi, 1992); Sardinians (Imanishi, 1992); Italians (Imanishi, 1992); French (Imanishi, 1992); Spanish (Arnaiz-Villena, 1997); Spanish-Basque (Arnaiz-Villena, 1997); Algerians (Arnaiz-Villena, 1995); Moroccan-Bereberes (Izaabel, 1998); Moroccans (Gomez-Casado, 2000) ; Western Samoa (Gao, 1992); Madang (Gao, 1992); Rabaul (Gao, 1992); New Caledonia (Gao, 1992)...…”
Section: Methodsmentioning
confidence: 97%
“…Sixty-seven other populations were included in the analyses for genetic comparisons and are detailed in the footnote of Figure 2; they come from different worldwide geographical locations (South, Central and North America, Mediterranean, East Asia, Australia and Pacific Islands) and belong to different ethnic groups (Amerindians, Siberian, Na-Dene, Eskimos, Caucasoids, Orientals, Australian aborigins, Polynesians, Melanesians and Micronesians). Populations used for study are: Mazatecos (Arnaiz-Villena, 2000); Seri (Petzl-Erler, 1997); Mixe (Petzl-Erler, 1997); Mixteco (Petzl-Erler, 1997); Zapoteco (Petzl-Erler, 1997); Mexican Mestizo (Unpublished); Arhuaco (Yunis, 1994); Kogi (Yunis, 1994); Arsario (Yunis, 1994); Cayapa (Titus- Trachtenberg, 1994); Xavante (Cerna, 1993); Guarani (Petzl-Erler, 1997); Toba-Pilaga (Cema, 1993) ; Mataco-Wichi (Cerna, 1993); Eastern-Toba ( Cerna, 1993); Jaidukama (Unpublished); Eskimos (Grahovac, 1998); Athabascans (Monsalve, 1998); Tlingit (Imanishi, 1992); Nivkhs (Grahovac, 1998); Udegeys (Grahovac, 1998); Koryaks (Grahovac, 1998); Chukchi ( Grahovac, 1998); Kets (Grahovac, 1998); Evenks (Imanishi, 1992); Singapure-Chinese (Imanishi, 1992); Buyi ( Imanishi, 1992); Manchu (Geng, 1995); Coreans (Imanishi, 1992); Japonese (Imanishi, 1992a,b); Khalk-Mongolians (Munkhbat, 1997); Tuvins (Martinez-Laso, 2001); Khoton-Mongolians (Munkhbat, 1997); Germans (Imanishi, 1992); Sardinians (Imanishi, 1992); Italians (Imanishi, 1992); French (Imanishi, 1992); Spanish (Arnaiz-Villena, 1997); Spanish-Basque (Arnaiz-Villena, 1997); Algerians (Arnaiz-Villena, 1995); Moroccan-Bereberes (Izaabel, 1998); Moroccans (Gomez-Casado, 2000) ; Western Samoa (Gao, 1992); Madang (Gao, 1992); Rabaul (Gao, 1992); New Caledonia (Gao, 1992)...…”
Section: Methodsmentioning
confidence: 97%
“…Such an attempt is valuable and would greatly benefit our understanding of the origin and the formation of Chinese populations. Several studies focusing on frequencies of HLA alleles and haplotypes have been reported [3][4][5][6][7][8][9][10]. However, the frequency data for HLA class I genes at allele level remain limited for the Chinese ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of two subtypes, DP0401 and DP0402, which differ from each other by 3 amino acids. Preliminary reports have shown that the presence of both DP0401 and DP0402 occurs at a frequency of 50% in Europe, 60% in South America, 80% in North America, 60% in India, 40% in the Xinjiang district in China, 25% in Africa and 15% in Japan [14], [15]. Interestingly, some reports have suggested that antigen presentation by HLA-DP4 molecules may be critical for viral elimination and that such antigen presentation plays an important role in the pathogenesis of chronic hepatitis B infection [16], [17].…”
Section: Introductionmentioning
confidence: 99%